The Effect of NaFeEDTA as an Iron Fortificant an Hematocrit and Blood Platelet Levels of Rats (Rattus norvegicus L.) Sprague-dawley Strain - Nova Anita; Agustino Zulys; Amelia Rosvita; Aisyah Safrina (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
The potential of NaFeEDTA as an iron fortificant can be assessed by identifying hemoglobin and red blood cell levels and their relationship to hematocrit levels. High hematocrit values can affect blood circulation. Iron can also affect platelet levels, excessive platelet aggregation can inhibit blood flow. This study aims to identify hematocrit and blood platelet levels of rats after NaFeEDTA in soy milk (SM). The method is RAL with 25 male rats in 5 treatment groups: KK1 (without SM); KK2 (SM 10 mL/kgBW); KP1 (SM + NaFeEDTA 2.7 mg Fe/kgBW); KP2 (SM + NaFeEDTA 5.4 mg Fe/kgBW); KP3 (SM + NaFeEDTA 10.8 mg Fe/kgBW) for 14 days. Hematocrit was measured using a hematology analyzer (t0 and t14). ANOVA-LSD test (P <0.05) showed hematocrit increases in KK2, KP1, KP2, and KP3 compared to KK1, highest in KP2 (6.22%). NaFeEDTA significantly reduced platelet levels, highest decrease in KP2 (3.06% compared to KK1 and 2.81% compared to KK2). Despite the decrease, platelet levels remained normal. Thus, NaFeEDTA has the potential to fortify iron absorption at an optimal dose of 5.4 mg Fe/kgBW.